The Mediating Effects of Social Support and a Grateful Disposition on the Relationship between Life Stress and Anger in Korean Nursing Students - Won Hee Jun; Jinhyang Yang; Eun Ju Lee (Elsevier, 2018)
Purpose: Anger management is a very important issue for nursing education. However, there is a lack of research identifying related factors. This study examined the mediating effects of social support and a grateful disposition on the relationship between life stress and anger in nursing students. Methods: The participants were 172 nursing students recruited from two universities in cities in South Korea. Baron and Kenny's regression method and the Sobel test were used to analyze the mediating effects of social support and a grateful disposition on the association between life stress and anger. Results: There were significant correlations between life stress, social support, a grateful disposition, and anger. In addition, social support and a grateful disposition exerted full mediating effects on the relationship between life stress and anger. Conclusion: Based on this study's results, enhancing social support and grateful disposition could help nursing students who experience anger resulting from life stress to manage their anger effectively. This finding suggests that, as specific strategies for anger management, nursing educators should encourage nursing students to use sources of social support and to engage in various gratitude activities. Keywords: anger management therapy, students, nursing, protective factors, social support